Imiquimod‐induced apoptosis of melanoma cells is mediated by ER stress‐dependent Noxa induction and enhanced by NF‐κB inhibition. Issue 2 (18th November 2015) - El‐Khattouti, Abdelouahid; Selimovic, Denis; Hannig, Matthias; Taylor, Erin B.; Abd Elmageed, Zakaria Y.; Hassan, Sofie Y.; Haikel, Youssef; Kandil, Emad; Leverkus, Martin; Brodell, Robert T.; Megahed, Mosaad; Hassan, Mohamed
Abstract: Melanoma is characterized by dysregulated intracellular signalling pathways including an impairment of the cell death machinery, ultimately resulting in melanoma resistance, survival and progression. This explains the tumour's extraordinary resistance to the standard treatment. Imiquimod is a topical immune response modifier (imidazoquinoline) with both antiviral and antitumour activities. The mechanism by which imiquimod triggers the apoptosis of melanoma cells has now been carefully elucidated. Imiquimod‐induced apoptosis is associated with the activation of apoptosis signalling regulating kinase1/c‐Jun‐N‐terminal kinase/p38 pathways and the induction of endoplasmic stress characterized by the activation of the protein kinase RNA‐like endoplasmic reticulum kinase signalling pathway, increase in intracellular Ca 2+ release, degradation of calpain and subsequent cleavage of caspase‐4. Moreover, imiquimod triggers the activation of NF‐κB and the expression of the inhibitor of apoptosis proteins (IAPs) such as, X‐linked IAP (XIAP) together with the accumulation of reactive oxygen species (ROS). Also, imiquimod triggers mitochondrial dysregulation characterized by the loss of mitochondrial membrane potential (Δψm), the increase in cytochrome c release, and cleavage of caspase‐9, caspase‐3 and poly(ADP‐ribose) polymerase (PARP). Inhibitors of specific pathways, permit the elucidation of possible mechanisms of imiquimod‐induced apoptosis. They demonstrate that inhibition of NF‐kB by the inhibitor of nuclear factor kappa‐B kinase (IKK) inhibitor Bay 11‐782 or knockdown of XIAP induces melanoma apoptosis in cells exposed to imiquimod. These findings support the use of either IKK inhibitors or IAP antagonists as adjuvant therapies to improve the effectiveness topical imiquimod in the treatment of melanoma.